Photon transmission technique to study phase transitions of poly(n-isopropylacrylamide) gels - Pekcan, Ö; Kara, S. (World Scientific Pub Co Pte Lt, 2004)
Temperature sensitive PNIPA Poly(N-isopropylacrylamide) gels were prepared by free-radical crosslinking copolymerization (FCC) of NIPA in the presence of various N,N'-methylenebisacrylamide (Bis) contents in water. FCC were carried out separately at various onset temperatures, T on (20, 22 and 24°C) for each Bis content gel. The photon transmission technique was used to study the demixing processes of these PNIPA gels at various wavelengths (450, 500, 550, 600, 690 nm). During the phase transition experiments, the temperatures of the gel samples increased from 24°C to 38°C with 0.4°C/min rate. It was observed that transmitted photon intensities I tr decreased dramatically around 34°C for almost all gel samples prepared at various onset temperatures in different Bis contents. The decrease in I tr was attributed to the increase in scattered light intensity I sc during demixing process. The behavior of I sc was modeled using Rayleigh's equation where the inverse power of wavelength λ was measured to interpret the demixing in water–PNIPA gel system. It was observed that large clusters are formed above demixing temperature, T d and it was understood that the PNIPA gel prepared at high T on presents low T d values.
Keywords: System; PNIPA Gel; Swollen Networks; Water; Demixing Temperature; Real-Time; Phase Transition; Turbidity; Spinodal Decomposition; Swelling Behavior; Acrylamide Gels; Liquid-Crystal; Methyl-Ether)